Ultralight Magnetic and Dielectric Aerogels Achieved by Metal–Organic Framework Initiated Gelation of Graphene Oxide for Enhanced Microwave Absorption - Huang, Xiaogu; Wei, Jiawen; Zhang, Yunke; Qian, BinBin; Jia, Qi; Liu, Jun; Zhao, Xiaojia; Shao, Gaofeng (Nano-Micro Letters, 2022)
The development of a convenient methodology for synthesizing the hierarchically porous aerogels comprising metal–organic frameworks (MOFs) and graphene oxide (GO) building blocks that exhibit an ultralow density and uniformly distributed MOFs on GO sheets is important for various applications. Herein, we report a facile route for synthesizing MOF/reduced GO (rGO) aerogels based on the gelation of GO, which is directly initiated using MOF crystals. Free metal ions exposed on the surface of MIL-88A nanorods act as linkers that bind GO nanosheets to a three-dimensional porous network via metal–oxygen covalent or electrostatic interactions. The MOF/rGO-derived magnetic and dielectric aerogels Fe3O4@C/rGO and Ni-doped Fe3O4@C/rGO show notable microwave absorption (MA) performance, simultaneously achieving strong absorption and broad bandwidth at low thickness of 2.5 (− 58.1 dB and 6.48 GHz) and 2.8 mm (− 46.2 dB and 7.92 GHz) with ultralow filling contents of 0.7 and 0.6 wt%, respectively. The microwave attenuation ability of the prepared aerogels is further confirmed via a radar cross-sectional simulation, which is attributed to the synergistic effects of their hierarchically porous structures and heterointerface engineering. This work provides an effective pathway for fabricating hierarchically porous MOF/rGO hybrid aerogels and offers magnetic and dielectric aerogels for ultralight MA. Highlights: 1 Metal–organic frameworks (MOFs) are used to directly initiate the gelation of graphene oxide (GO), producing MOF/rGO aerogels. 2 The ultralight magnetic and dielectric aerogels show remarkable microwave absorption performance with ultralow filling contents.